DEPRESSION AND ANXIETY IN PATIENTS WITH CARDIOVASCULAR DISEASES: A NARRATIVE REVIEW OF PREVALENCE, MECHANISMS AND CLINICAL IMPLICATIONS - Natalia Sitko; Paulina Makowska; Joanna Gontarczyk; Alicja Laske; Martyna Sowa; Antoni Majda; Julia Pająk; Kacper Kucharski; Anna Kamosińska; Adam Kowal; Julia Sokołowska; Marcel Dawidowicz (International Journal of Innovative Technologies in Social Science, 2026)
Background: Cardiovascular diseases (CVD), including coronary artery disease, heart failure, and atrial fibrillation, remain major causes of morbidity and mortality worldwide. Depression and anxiety are highly prevalent in these populations and are associated with impaired quality of life, reduced functional status, and worse clinical outcomes.Objective: This narrative review aimed to summarise current evidence on the prevalence, prognostic significance, and underlying mechanisms of depression and anxiety in patients with cardiovascular disease, and to discuss major diagnostic challenges, screening strategies, and treatment approaches relevant to clinical practice.Methods: A narrative review of the literature was conducted using PubMed as the primary database, supplemented by searches in PubMed Central, Google Scholar, and selected open-access journals. Priority was given to meta-analyses, systematic reviews, clinical reviews, consensus statements, and key prospective or interventional studies published mainly between 2000 and early 2026, with a focus on coronary artery disease, heart failure, and atrial fibrillation. The review primarily emphasised studies published from 2020 onward, while earlier landmark papers were included when considered essential for contextual understanding.Results: Depression and anxiety are common across major cardiovascular conditions and are associated with increased risks of incident cardiovascular disease, recurrent events, mortality, hospitalisation, and reduced health-related quality of life. Proposed mechanisms include autonomic and hypothalamic- pituitary-adrenal axis dysregulation, inflammation, endothelial dysfunction, platelet activation, and adverse health behaviours. Diagnostic overlap between cardiac and psychological symptoms contributes to underrecognition. Brief screening instruments such as the PHQ‑9, GAD‑7, and HADS appear feasible in routine care when linked to structured follow‑up. Psychological interventions, selected antidepressants, and collaborative care models may improve mental health outcomes, although evidence for their effects on hard cardiovascular endpoints remains limited.Conclusions: Depression and anxiety are clinically important comorbidities in cardiovascular disease and should be systematically addressed in cardiovascular care. Integrating mental health screening and multidisciplinary management into routine practice may enhance overall patient outcomes.